2016
DOI: 10.1093/jopart/muw057
|View full text |Cite
|
Sign up to set email alerts
|

Building Collaboration: Examining the Relationship between Collaborative Processes and Activities

Abstract: This study investigates if the collaborative process differs among a group of public programs involved in varying levels of interorganizational activities. Thomson and Perry (2006) suggest five process dimensions underlie collaboration: governance, administration, norms of trust, mutuality, and organizational autonomy. While these dimensions are clearly unique, it is unclear if any of these dimensions are necessary or sufficient for varying degrees of interorganizational involvement. Inventorying the interorga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 22 publications
3
25
0
6
Order By: Relevance
“…Similar findings were reported by Sedgwick (2016) who studied the collaboration among a range of publicly funded program service providers. She found that strong single-member accountability has clear implications for the outcomes of the network as a whole as it prevents strong inter-organizational relationships and undermines the integration of missions and tasks, and collaborative service provision.…”
Section: Conclusion and Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Similar findings were reported by Sedgwick (2016) who studied the collaboration among a range of publicly funded program service providers. She found that strong single-member accountability has clear implications for the outcomes of the network as a whole as it prevents strong inter-organizational relationships and undermines the integration of missions and tasks, and collaborative service provision.…”
Section: Conclusion and Discussionsupporting
confidence: 85%
“…Schools who are predominantly held accountable for their own performance have few incentives to participate in comprehensive joint planning and sharing of risks or to give up autonomy to a network-level authority. A lack of alignment in single-member and network-level accountability creates tensions for particularly high performing schools who have to fulfil both organizational goals (set by single school inspections) and collaborative goals (supporting peers in special measures), thus juggling organizational and collaborative identities (Sedgwick 2016).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…More recently, the perspective of a unilateral policymaking process is increasingly being replaced by collective decision-making involving public and private sectors (Ansell & Gash, 2007). In this scenario, public administration has to find ways to achieve collaboration across multiple public units through collaboration within the public sector (Cabral & Krane, 2018;Sedgwick, 2017). Notwithstanding, the solutions are not only concentrated within public bureaucracies.…”
Section: Public Administration and The Responses To Covid-19 Outbreakmentioning
confidence: 99%
“…Considering the difficulties and contentions of measuring goal intertwinement and public value in the evaluation of cooperation, Sedgwick [22] looks at inter-organizational activities as outcomes of cooperation. Inter-organizational activities are interactions between a set of interdependent actors in a specific policy field.…”
Section: Inter-organizational Activities As Outcomes Of Cooperationmentioning
confidence: 99%
“…This study follows in the approach by Sedgwick [22] and acknowledges that inter-organizational activities are concrete outcomes of cooperation; and that the intensity of inter-organizational activities is a manifestation of effective cooperation. To specify variation in inter-organizational activities, this study adopts the framework by Mandell and Keast [23], which distinguish three levels of intensity of the inter-organizational activities.…”
Section: Inter-organizational Activities As Outcomes Of Cooperationmentioning
confidence: 99%